1923 Ind. Acts 108 - (:unkn) unknown (My University, 1923)
Intoxicating Liquor-Transportation Penalty, ch. 34, § 1: Prohibited transporting liquor in wagon, buggy, automobile, or water or aircraft when such vehicle has any firearms or guns within. Violators guilty of a felony, fined not more than one thousand dollars and imprisoned not less than one year nor more than two years.
Keywords: TRANSFER & POSSESSION